Employee Recruitment and Development Process: Implementation of Islamic Values - Husainah, Nazifah; Maswanto; Yusuf, M; Hidayah, Nur; Putra, Muhammad Dipo Alam Panai (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the implementation and suitability of employee recruitment and development applied at Islamic banks in South Tangerang with Islamic values. This research included qualitative descriptive research. Data collection techniques used by means of interviews and documentation. The results showed that the recruitment process at Bank Islam in South Tangerang used a closed method by prioritizing moral values (attitudes) and honesty of these employees. In recruitment that uses closed methods is also less in accordance with Islamic values because it tends to lead to elements of nepotism. So that the employee recruitment process is still less selective. From the employee development process at the Bank, Bank Islam in South Tangerang really realized that valuable assets in the company are employees within the company environment. Training and development applied to Bank bak Islam in South Tangerang not only prioritizes the potential and quality of employees, but Bank Bank Islam in South Tangerang also provides training and development in the form of moral and spiritual.